PEMODELAN GENERATOR PLASMA HIDROGEN FREKUENSI GELOMBANG MIKRO TEKANAN ATMOSFIR - Reeky Fardinata; Saktioto Saktioto; Rakhmawati Farma (Universitas Riau, 2023)
The model used in this work is a two-dimensional fluid plasma model coupled with Maxwell equations at atmospheric pressure. The model was created by applying different plasma torch parameters using the finite element approach. Three separate stages of the numerical modeling were used to show how the increase in electron density increases with time. It may be inferred from the molecular ion distribution features that the torch's quartz tube's port, which is larger than the tube's center, is where the molecular ions are primarily disseminated. Reduced pressure and the calculated distance from the port to the center of the quartz tube result in a drop in the density ratio of molecular ions to electrons. The research on microwave plasma properties revealed that atmospheric pressure is important for modeling and developing plasma sources, particularly for the conversion of carbon dioxide.